Intrauterine Versus External Tocodynamometry in Monitoring Labour: A Randomised Controlled Clinical Trial. Issue 5 (May 2021) - Hautakangas, T.; Uotila, J.; Huhtala, H.; Palomäki, O.
Abstract : (Abstracted from BJOG 2020;127:1677–1686) Intrauterine tocodynamometry (IT) and external tocodynamometry (ET) are used clinically to monitor contractions during labor and guide the use of oxytocin in prolonged labor. Four randomized controlled trials (RCTs), conducted over 20 years ago, compared IT with ET in women who were given oxytocin to induce or augment labor but did not have a previous cesarean delivery (CD).